Politics of Peace Agreement Implementation - Bala, Sajib. author. aut Link
XXII, 221 p. 6 illus., 2 illus. in color.
Keywords: Dr. Sajib Bala is Associate Professor, Department of International Relations, Jahangirnagar University, Bangladesh. This book analyses why is it that the different actors, namely the GoB, the Hill people and the international community, hold different views about the CHT Peace Agreement and the question of its implementation. It is based on a qualitative research study using methodological triangulation of both primary and secondary data. The author scrutinizes the underlying facts regarding the implementation politics (or interest) of the CHT Peace Agreement. .